Data ecryption based on multi-order FrFT, and FPGA implementation of DES algorithm - A. Rabie; Kh. El Shafie; A. Hammuoda; M. Rohiem (Institute of Advanced Engineering and Science, 2020)
Cryptography techniques need some algorithms for encryption of data. Most of available encryption techniques are used for textual data; a few of encryption methods are used for multimedia data; However, This Algorithms that are used for textual data may not be inefficient for multimedia, because it is size is greater than the text. Therefore, Cryptosystems need to find and develop a new encryption schemes for such data. The most popular symmetric key algorithms are Data Encryption Standard (DES). However, DES is may be not suitable for multimedia because it consumes times. Encryption and decryption of these data require different methods. In this paper a method for encryption/decryption data by using the nature of FrFT in signals analysis, based on multi-order Fractional Fourier Transform has been introduced. The security of the method used in the encryption work was taken into account to identify the different indicators to measure the security of the encryption Techniques. These indicators are: sensitivity proposed Techniques for the key, the complexity of the processes, and statistical analysis. The key is formed by combination of order of Fractional Fourier Transform. The encrypted data is obtained by the summation of different orders. Numerical simulation results are given to demonstrate this proposed method.